Implementation of a Stewardship Initiative on Respiratory Viral PCR‐based Antibiotic Deescalation. Issue 6 (20th May 2019) - Srinivas, Pavithra; Rivard, Kaitlyn R.; Pallotta, Andrea M.; Athans, Vasilios; Martinez, Kristin; Loutzenheiser, Samantha; Lam, Simon W.; Procop, Gary W.; Richter, Sandra S.; Neuner, Elizabeth A.
Abstract : Objective: Respiratory viral polymerase chain reaction (RV PCR) tests assist in rapidly identifying viral pathogens and differentiating viral versus bacterial causes of pneumonia. Studies evaluating the use of RV PCR tests on antibiotic use in adults have demonstrated mixed results. We implemented an antimicrobial stewardship (ASP) intervention for patients with a positive RV PCR test result who were receiving broad‐spectrum antibiotics and aimed to assess the impact on antibiotic usage. Methods: Retrospective quasi‐experimental study of adult hospitalized patients comparing time to antibiotic deescalation, duration of antibiotic therapy, and antiviral use preintervention (January–March 2016) and postintervention (January–March 2017). Results: Of 172 ASP alerts reviewed, 55 (32%) were considered actionable. Of these, 47% of interventions were accepted. No significant difference was observed in median time to antibiotic deescalation (pre: 2.7 days vs post: 2.3 days, p=0.88). Time to discontinuation of antimicrobial therapy pre‐ and postintervention was reduced from 4 to 1.9 days (p=0.057) for piperacillin‐tazobactam, from 2.7 to 1.8 days (p=0.75) for ceftriaxone, and from 3.6 to 2 days (p=0.4) for levofloxacin, respectively. Time to initiation of oseltamivir for influenza was significantly shorter in the postintervention group (pre: 11.3 hrs vs post: 3.6 hrs, p=0.02). Conclusion: A third of patients receiving broad‐spectrum antibiotics with a positive RV PCR had an opportunity for antimicrobial optimization, although this did not translate into a significant impact on the time to antibiotic deescalation or overall antibiotic use. Combination of RV PCR results with biomarkers to rule out bacterial coinfections and chest radiographic findings may help enhance the likelihood of accepted antibiotic deescalation recommendations and represents an area of future research.